INTERVENTION OF BANANA WEEVIL MOLECULES AND HUSK CHARCOAL FOR THE VEGETATIVE PHASE OF PAPAYA SEEDS (CARICA PAPAYA L.) - Pasca Sari, Desi Sri; Sebayang, Nico Syahputra (Jurnal Pertanian, 2020)
Papaya is one of the promising agricultural products. To increase Papaya production, we use organic fertilizers that are easily available and are often wasted by Southeast Aceh farmers. Our research aims to determine the effect of rice husk charcoal and banana weevil MOL on papaya seedlings (Carica Papaya L.). honey. This research was conducted in Alur Buluh Village, Southeast Aceh District, with a height of ± 245 m above sea level, which was carried out for 2 months. The design used was a Randomized Block Design (RBD) with two treatment factors, namely: Factor I: rice husk charcoal (A) consisting of 3 levels, namely: A0: 0 g / plant / 1,100g soil; A1: 150g / plant / 1,250g of soil; A2: 200 g / plant / 1,300g of soil. Factor II: MOL fertilizer for banana weevil (M) consisting of 3 levels, namely: M0: 0 ml / liter of water / plot; M1: 10 ml / liter of water / plot; M2: 30 ml / liter of water / plot. Variance analysis test results showed that the treatment level of rice husk charcoal dose had a very significant effect on plant height at 3 MSPB, 4 MSPB and 5 MSPB and stem diameters of 1, 3, 4, 5 and 6 MSPB. Whereas 2 and 6 MSPB significantly affected plant height, and stem diameter at 2 MSPB significantly affected. The effect of MOL administration of banana weevil has a very significant effect on plant height at ages 2 and 3 MSPB, stem diameter at 3 MSPB. In the interaction of the treatment of husk charcoal and MOL fertilizer the banana weevil had a very significant effect on the diameter of the stem at the age of 3 MSPB, and the stem diameter of 4 MSPB. We conclude the use of fertilizers derived from husk charcoal and banana weevil Mol are good for the growth of papaya seeds.